2016
DOI: 10.1111/1346-8138.13707
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of multiple in‐transit melanomas on the leg with intensity‐modulated radiotherapy and immune checkpoint inhibitors: Report of two cases

Abstract: Because the efficacy rates of monotherapy with immune checkpoint inhibitors such as nivolumab or ipilimumab are not sufficient, to enhance the antitumor effects of these reagents is of great interest among dermato-oncologists. In this report, we describe two cases of multiple in-transit metastatic melanomas on the leg successfully treated with intensity-modulated radiotherapy (IMRT) using a CyberKnife in combination with ipilimumab or nivolumab. Our cases suggested that IMRT could enhance the antitumor effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…For the patients with anti‐PD‐1 Ab‐failed advanced melanoma, ipilimumab is another choice, especially for melanoma without the BRAF gene mutation . However, because the efficacy of ipilimumab in patients with nivolumab‐resistant melanoma is extremely low after objective tumor progression, radiotherapy is sometimes administrated in combination with ipilimumab . Interestingly, Chandra et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the patients with anti‐PD‐1 Ab‐failed advanced melanoma, ipilimumab is another choice, especially for melanoma without the BRAF gene mutation . However, because the efficacy of ipilimumab in patients with nivolumab‐resistant melanoma is extremely low after objective tumor progression, radiotherapy is sometimes administrated in combination with ipilimumab . Interestingly, Chandra et al .…”
Section: Discussionmentioning
confidence: 99%
“…10 However, because the efficacy of ipilimumab in patients with nivolumab-resistant melanoma is extremely low after objective tumor progression, 5 radiotherapy is sometimes administrated in combination with ipilimumab. 11 Interestingly, Chandra et al 12 reported that ipilimumab increases the abscopal response of low-dose radiotherapy, suggesting that radiotherapy is needed for ipilimumab monotherapy for advanced melanoma without the BRAF gene mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint inhibitors, such as nivolumab and ipilimumab, significantly prolong the overall survival and improve the response rate of unresectable metastatic melanoma [ 1 , 2 , 3 ]. Therefore, the enhancement of antitumor effects of anti-PD-1 antibody has been widely investigated [ 1 , 2 , 3 , 4 , 5 , 6 ]. Indeed, Larkin et al [ 1 ] reported that the rate of overall survival at 3 years was 52% in the nivolumab group and 34% in the ipilimumab group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some recent clinical studies showed that the combination of RT and ipilimumab increased the response and survival rates of patients with brain metastasis of melanoma . However, studies on combined anti‐PD‐1 therapy and RT are limited . Moreover, the efficacy of combined RT and anti‐PD‐1 treatment for acral and mucosal melanoma is unclear because of the rarity of these malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…4,8 However, studies on combined anti-PD-1 therapy and RT are limited. [9][10][11][12][13][14] Moreover, the efficacy of combined RT and anti-PD-1 treatment for acral and mucosal melanoma is unclear because of the rarity of these malignancies. Therefore, this study aimed to evaluate the efficacy of combined anti-PD-1 therapy (nivolumab or pembrolizumab) and RT in acral and mucosal melanoma.…”
Section: Introductionmentioning
confidence: 99%